A research on biogas-diesel dual fuel diesel engine - YILMAZ, İLKER TURGUT; GÜMÜŞ, METİN (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2017)
In the present study, cylinder pressures, brake specific fuel consumptions and exhaust emissions of a dual fuel diesel engine used biogas (% 60 CH4-% 40 CO2) as main fuel was examined experimentally. Experiments were conducted at 1750 rpm under 50 Nm, 75 Nm and 100 Nm loads. Results showed that biogas could be used in diesel engines for reducing soot emissions. HC emissions and maximum cylinder pressures increased for all engine loads with using biogas in diesel engine. NOx emission decreased at low engine load but increased depending on the rise of engine load. The modifications such as adjusting injection timing, decreasing compression ratio and using different lubrication oils can be used for not only increasing performance but also lowering exhaust emissions of a biogas-diesel dual fuel engine.
Keywords: Biogas; dual fuel diesel engine; fuel consumption; exhaust emissions; SPARK-IGNITION ENGINE; INTERNAL-COMBUSTION ENGINES; EMISSION CHARACTERISTICS; SIMULATED BIOGAS; NATURAL-GAS; PERFORMANCE; HYDROGEN; MODE; INJECTION; CNG